2022
DOI: 10.1021/acs.jafc.1c07658
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Tartary Buckwheat-Derived Nanovesicles on Gut Microbiota

Abstract: Evidence suggests that plant-derived nanovesicles may play a significant role in human health. Tartary buckwheat has several physiological activities; however, its underlying health-promoting mechanism remains unclear. In this study, first, Tartary buckwheat-derived nanovesicles (TBDNs) were collected, their structures were analyzed, and microRNA sequencing was performed. Next, target prediction and functional verification were conducted. Finally, the effects of TBDNs on gut microbiota and short-chain fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…The method described by Liu et al (Liu et al, 2022 ) was used to determine the SCFAs content. Briefly, the fermentation broth was centrifuged and added to the anhydrous ethanol in a 1:1 ratio, vortexed, mixed, and centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…The method described by Liu et al (Liu et al, 2022 ) was used to determine the SCFAs content. Briefly, the fermentation broth was centrifuged and added to the anhydrous ethanol in a 1:1 ratio, vortexed, mixed, and centrifuged.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, they can facilitate the growth of partial bacteria such as Firmicutes , Tenericutes , and Lachnospiraceae . Liu et al demonstrated that Tartary buckwheat-derived ELNs can target functional genes related with the physiological processes of Escherichia coli and Lactobacillus rhamnosus , promote the growth of E. coli and L. rhamnosus , and enhance the diversity of intestinal microorganism.…”
Section: Intestinal Barrier Improvementmentioning
confidence: 99%
“…Particularly, they can facilitate the growth of partial bacteria such as Firmicutes, Tenericutes, and Lachnospiraceae. Liu et al 74 demonstrated that Tartary buckwheat-derived ELNs can target functional genes related with the physiological processes of Escherichia coli and Lactobacillus rhamnosus, promote the growth of E. coli and L. rhamnosus, and enhance the diversity of intestinal microorganism. In addition, a similar study carried out by Teng et al 25 reported that miRNAs inside of ginger-derived ELNs were selectively taken up by bacteria of Lactobacillus rhamnosus and further regulated the expression of related bacterial genes included in the improvement of colitis in DSS-induced mouse models.…”
Section: ■ Intestinal Barrier Improvementmentioning
confidence: 99%
“…Metal-free PDNPs are environmental friendly, toxic chemical free, cheap, and energy serving ( Kharissova et al, 2019 ; Surendran et al, 2021 ). The potential to derive metal-free NPs with medicinal properties from plants has gained more attention worldwide ( Zhang et al, 2016 ; Saravanan et al, 2021 ; Surendran et al, 2021 ; Liu et al, 2022 ; Nemidkanam and Chaichanawongsaroj, 2022 ). Liu et al (2022) reported the therapeutic ability of metal-free PDNPs on gut microbiota while Xiao et al (2018) highlighted the therapeutic efficacy of metal-free NPs synthesized from 11 edible fruits and vegetables.…”
Section: Alternative Therapeutic Approaches and Strategies For Multid...mentioning
confidence: 99%
“…The potential to derive metal-free NPs with medicinal properties from plants has gained more attention worldwide ( Zhang et al, 2016 ; Saravanan et al, 2021 ; Surendran et al, 2021 ; Liu et al, 2022 ; Nemidkanam and Chaichanawongsaroj, 2022 ). Liu et al (2022) reported the therapeutic ability of metal-free PDNPs on gut microbiota while Xiao et al (2018) highlighted the therapeutic efficacy of metal-free NPs synthesized from 11 edible fruits and vegetables. Saravanan et al (2021) reported the antibacterial efficacy of metal-free NPs derived from Curcuma longa plant against E. coli, S. aurous, K. pneumoniae, and S. epidermidis .…”
Section: Alternative Therapeutic Approaches and Strategies For Multid...mentioning
confidence: 99%